👤


1) (5×2-8×+6)-(3×2-3×+2)=________
2)(2×2-9×-2)(×-3)=___________
3)×2+7×+12÷×+4=____________




Paki Answer po Need ko na kasi eh


Sagot :

1.

(5x² - 8x + 6) - (3x² - 3x + 2)

remove the parentheses:

5x² - 8x + 6 - 3x² + 3x - 2

collect like terms:

2x² - 5x + 6 - 2

subtract the numbers:

= 2x² - 5x + 4

2.

(2x² - 9x - 2) × (x - 3)

use the distributive property:

2x²(x - 3) - 9x(x - 3) - 2(x - 3)

remove the parentheses:

2x³ - 6x² - 9x² + 27x - 2x + 6

collect like terms:

= 2x³ - 15x² + 25x + 6

3.

(x² + 7x + 12) ÷ (x + 4)

rewrite:

x² + 7x + 12/x + 4

rewrite the expression:

x² + 4x + 3x + 12/x + 4

factor the expressions:

x(x + 4)+ 3(x + 4)/x + 4

factor the expression:

(x + 4) × (x + 3)/x + 4

reduce the fraction with x + 4:

= x + 3